Implementing collaborative learning in practice in a London maternity ward. - Markowski, Marianne; Yearley, Carole; Bower, Heather; Hayford, Wilhelmina; Rugge, Ethel; Chatterley-Stettler, Susanne (British Journal of Midwifery, 2022)
A collaborative learning in practice pilot study in a maternity unit in a London Trust has been carried out. Collaborative learning in practice is a model for supervising students where they work in small groups under the guidance of a practice supervisor. The pilot found that the model is a possible approach to increasing placement capacity that provides an equally enriching, if not improved, learning experience. Improvements were seen in peer support, confidence and responsibility, teamwork skills, new learning opportunities and being better prepared for practice after graduation. Reflecting on the experience of implementing the first cycle of the pilot, this article provides guidance to healthcare education providers for implementing the model in practice placements. The guidance offers a modified model, establishing key personnel as collaborative learning in practice champions and providing adequate preparation for students, staff and the environment.